Staggering Effects in Nuclear and Molecular Spectra - Bonatsos, Dennis; Daskaloyannis, C.; Drenska, S. B.; Karoussos, N.; Maruani, J.; Minkov, N.; Raychev, P. P.; Roussev, R. P. (HNPS Advances in Nuclear Physics, 2019)
It is shown that the recently observed AI = 2 staggering seen in superdeformed nuclear bands is also occurring in certain electronically excited rotational bands of diatomic molecules, in which it is attributed to interband interactions (bandcrossings). In addition, a AI = 1 staggering effect (i.e. a relative displacement of the levels with even angular momentum I with respect to the levels of the same band with odd /) is seen in molecular bands free from AI = 2 staggering (i.e. free from interband interactions/bandcrossings). The magnitude of the AI = 1 staggering is found to be constant as a function of 7, in agreement with the predictions of algebraic models (u(ll) model, u(16) model, Vector Boson Model) used for the description of octupole nuclear bands, i.e. bands corresponding to pear-like shapes, suggesting that the presence of AI = 1 staggering in rotational bands of diatomic molecules could be attributed in general to the inequality of the masses of the two atoms of which the molecule is composed. The existence of the AI = 1 staggering effect is corroborated by the fact that separate Dunham expansions for the even levels and the odd levels of such bands give similar but different parameter sets.